Effects of coil diameter in thickness measurement using pulsed Eddy Current non-destructive testing - Azaman, Khairun Nisa; Sophian, Ali; Nafiah, Faris (IOP Publishing, 2017)
Many applications would benefit from a cost effective 3D position or distance measurement systems. Stereo vision systems may offer this functionality with the extra benefits when the images are used for other purposes as well, such as object recognition. In this paper, an accuracy evaluation method of two stereo-vision systems, which use a coordinate measuring machine (CMM) and a reference block, has been presented, and the results have also been presented for systems using infra red cameras and webcams. Following a calibration process, the two systems were used in determining the dimensions of the reference block. The results show that the method could evaluate the two systems. While the evaluation results show that the webcams have a better accuracy and precision, the leap motion controller can be used when shorter measurement distance are required, thanks to their shorter lens distance and wide-angle lenses.